2007
DOI: 10.1149/1.2408938
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Copper Oxidation in Alkaline Mediums with α-Alanine and Asparagine Acid Additives

Abstract: It was investigated α-alanine and asparagine acid influence on copper anodic process kinetics in alkaline electrolytes. The experiments were carried out at two systems: I -0.01 M NaOH +X M α-Ala (X=10 -4 ÷10 -1 M) and II -0.01 M NaOH +X M Asp (X=10 -5 ÷10 -3 M). It was found out that α-alanine (from С Ala = 5×10 -3 М to 2×10 -2 М) and asparagine acid (from С Asp =1×10 -5 to 1×10 -3 М) stimulate anodic processes at passive region and cause of metal local activation. However except this general regularity, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The obtained results have shown that in both background solutions copper undergoes local activation (LA) [1,2]. Under this pits have the view of etch-pits of spherical shape form on metal surface and its number was few (2-3 at working surface 7.85×10 -5 m 2 ).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The obtained results have shown that in both background solutions copper undergoes local activation (LA) [1,2]. Under this pits have the view of etch-pits of spherical shape form on metal surface and its number was few (2-3 at working surface 7.85×10 -5 m 2 ).…”
mentioning
confidence: 86%
“…Under this pits have the view of etch-pits of spherical shape form on metal surface and its number was few (2-3 at working surface 7.85×10 -5 m 2 ). Earlier local depassivation process mechanism at chosen background electrolytes was examined in details at [1,2] and it was interpreted as a nucleophile substitution reaction of passivator particles by amino acid (AA) anions of dissociative type (S N1 ) [3]. Addition of small concentrations of NaCl (1×10 -7 -1×10 -4 M) stabilizes investigated systems.…”
mentioning
confidence: 99%